Nursing intervention using ice gel pack for pain reduction during femoral sheath removal after cardiac catheterization - Davris, Wendo; Mailani, Fitri; Lenggogeni, Devia Putri (Institute of Computer Science (IOCS), 2025)
Cardiac catheterization is performed to reduce mortality risk from vascular stenosis. Following the procedure, femoral sheath removal often resulted in mild to severe pain. This study aimed to describe nursing care through the application of an ice gel pack as a nonpharmacological method to reduce pain during femoral sheath removal in post–cardiac catheterization patients at RSUP Dr. M. Djamil Padang. A case study design was applied, which included assessment, nursing diagnoses, intervention, implementation, and evaluation. The ice gel pack was applied over the sheath site for 20 minutes before sheath removal. Evaluation showed that pain intensity decreased from a scale of 5 to 3 after the intervention. The application of an ice gel pack effectively reduced pain and is recommended for inclusion in hospital standard procedures.